Peranan Transportasi Multimoda dan National Logistic Ecosystem (NLE) dalam Meningkatkan Daya Saing Logistik Nasional - Sitorus, Budi Santoso (Institut Transportasi dan Logistik Trisakti, 2022)
Multi-modal transport is an important component of the logistics system, since freight transport will be more efficient if it is carried out in a single document. The use of multimodal transportation is still less in demand by logistics businesses, because fewer assets owned by companies or entrepreneurs will cause costs for entrepreneurs. In the delivery of consumer goods require cheaper shipping costs, while on the part of the sender of the goods the necessary costs are means of transport and a short time, for that delivery rates based on volumetric goods. The problem of research is that there is over load, distribution inefficiency and there is no logistics platform from upstream to downstream. Research methods with qualitative descriptive approach, secondary data collection techniques obtained from various sources, and data analysis used is SWOT analysis.